Can the ability to adapt to exercise be considered a talent-and if so, can we test for it? - Craig Pickering; John Kiely (SpringerOpen, 2017)
Abstract Talent identification (TI) is a popular and hugely important topic within sports performance, with an ever-increasing amount of resources dedicated to unveiling the next sporting star. However, at present, most TI processes appear to select high-performing individuals at the present point in time, as opposed to identifying those individuals with the greatest capacity to improve. This represents a potential inefficiency within the TI process, reducing its effectiveness. In this article, we discuss whether the ability to adapt favorably, and with a large magnitude, to physical training can be considered a talent, testing it against proposed criteria. We also discuss whether, if such an ability can be considered a talent, being able to test for it as part of the TI process would be advantageous. Given that such a capacity is partially heritable, driven by genetic variation between individuals that mediate the adaptive response, we also explore whether the information gained from genetic profiling can be used to identify those with the greatest capacity to improve. Although there are some ethical hurdles which must be considered, the use of genetic information to identify those individuals with the greatest capacity appears to hold promise and may improve both the efficiency and effectiveness of contemporary TI programmes.